Biodegradable PTX-PLGA-coated magnesium stent for benign esophageal stricture: An experimental study. (1st July 2022) - Liu, Lin-Lin; Qin, Juan; Zeng, Chu-Hui; Du, Rui-Jie; Pan, Tao; Ji, Jia-Jie; Lu, Li-Gong; Chen, Lei; Liu, Dong-Fang; Yang, Jian; He, Shi-Cheng; Zhu, Hai-Dong; et al.
Abstract: Biodegradable stents can degrade step by step and thereby avoid secondary removal by endoscopic procedures in contrast to metal stents. Herein, a biodegradable composite stent, a magnesium (Mg)-based braided stent with a surface coating of poly (lactic-co-glycolic acid) (PLGA) containing paclitaxel (PTX), was designed and tested. By adding this drug-loaded polymer coating, the radial force of the stent increased from 33 Newton (N) to 83 N. PTX was continuously released as the stent degraded, and the in vitro cumulative drug release in phosphate-buffered saline for 28 days was 115 ± 13.5 μg/mL at pH = 7.4 and 176 ± 12 μg/mL at pH = 4.0. There was no statistically significant difference in the viability of fibroblasts of stent extracts with different concentration gradients ( P > 0.05), while the PTX-loaded stents effectively promoted fibroblast apoptosis. In the animal experiment, the stents were able to maintain esophageal patency during the 3-week follow-up and to reduce the infiltration of inflammatory cells and the amount of fibrous tissue. These results showed that the PTX-PLGA-coated Mg stent has the potential to be a safe and effective approach for benign esophageal stricture. Statement of significance: We designed a biodegradable composite stent, having poly (lactic-co-glycolic acid) (PLGA) containing paclitaxel (PTX) coated the surface of the magnesium (Mg)-based braided stent. We evaluated in vitro and in vivo characteristics of the Mg esophageal stent having a PLGA coating plus a variable concentration of PTX in comparison with the absence of PTX PLGA coating. The PTX PLGA stents exerted higher radial force than stents without coating, degraded more quickly in an acid medium, and effectively promoted fibroblast apoptosis in vitro experiments. In a rabbit model of caustic-induced esophageal stricture, there was an increased lumen and decreased inflammation of the esophageal wall in the animals stented with PTX-PLGA versus the sham group, indicating a potential approach for benign esophageal stricture. Graphical abstract: Image, graphical abstract